Design and application of a gynecological drainage tube pants (一种妇科留置引流管病号裤的设计) - WANG Ruilian (王瑞莲); LIU Xuejiao (刘雪姣); WU Chao (武超); RUAN Yanchao (阮艳超); LIU Shuang (刘爽) (Association of Integrative Nursing, 2022)
Clinically, drainage tubes and/or urinary catheters need to be indwelled in gynecological patients after surgery. When patients get out of bed, they often need to carry the drainage tube and/or bag by themselves or others, causing inconvenience and exposing their privacy. Therefore, the traditional pants for patients cannot meet the actual demand of patients with multiple drainage tubes who need to get out of bed. In order to solve this problem, this paper introduced a designed pair of pants for patients with gynecological indwelling drainage tube by optimizing the traditional ones. The pants not only can protect the privacy of patients, but also can fix the drainage tube and/or bag used by gynecological patients after surgery, facilitating patients' activities. In all, the pants help patients avoid the possible risks caused by multiple drainage tubes, and greatly improve the comfort of patients. They are worthy of popularization and application in the clinical nursing of gynecology. (妇科患者术后一般需留置引流管和/或尿管, 传统病号裤并不能满足对于有多条引流管的患者下床活动的实际需求。基于传统病号服现存的问题, 本研究设计了一种既能保护患者的隐私, 且能够固定妇科患者术后所使用的引流管以及引流袋的妇科留置引流管病号裤, 在患者活动度、预防相关风险等方面均有不错的表现, 值得在妇科的临床护理中推广应用。)